Effects of cooperative translation on Chinese EFL student levels of interest and self-efficacy in specialized English translation. Issue 3 (2nd April 2016) - Yang, Xianmin; Guo, Xiaoshan; Yu, Shengquan
Abstract : Translation instruction is very important in specialized English teaching activities. The effectiveness of current specialized English translation instruction (SETI) in mainland China, however, is unclear because university students have become less interested in, and less confident when doing, English translation. This study investigated the effects of online cooperative translation on EFL students' levels of interest and self-efficacy with respect to specialized English translation through a questionnaire, focus group interview, interaction data analysis, and pre-test and post-test on 48 second-year college students in China majoring in educational technology. The results showed that online cooperative translations could significantly increase student interest and self-efficacy in specialized English translation. In cooperative translation, student engagement was significantly and linearly correlated with their interest and self-efficacy in translation. We conclude with recommendations on reforming current SETI practices in mainland China's universities.